Human Cerebral Organoid Implantation Alleviated the Neurological Deficits of Traumatic Brain Injury in Mice. (22nd November 2021) - Bao, Zhongyuan; Fang, Kaiheng; Miao, Zong; Li, Chong; Yang, Chaojuan; Yu, Qiang; Zhang, Chen; Miao, Zengli; Liu, Yan; Ji, Jing
Abstract : Traumatic brain injury (TBI) causes a high rate of mortality and disability, and its treatment is still limited. Loss of neurons in damaged area is hardly rescued by relative molecular therapies. Based on its disease characteristics, we transplanted human embryonic stem cell- (hESC-) derived cerebral organoids in the brain lesions of controlled cortical impact- (CCI-) modeled severe combined immunodeficient (SCID) mice. Grafted organoids survived and differentiated in CCI-induced lesion pools in mouse cortical tissue. Implanted cerebral organoids differentiated into various types of neuronal cells, extended long projections, and showed spontaneous action, as indicated by electromyographic activity in the grafts. Induced vascularization and reduced glial scar were also found after organoid implantation, suggesting grafting could improve local situation and promote neural repair. More importantly, the CCI mice's spatial learning and memory improved after organoid grafting. These findings suggest that cerebral organoid implanted in lesion sites differentiates into cortical neurons, forms long projections, and reverses deficits in spatial learning and memory, a potential therapeutic avenue for TBI.